Note—A Note on “Substitution Effects in Geometric Programming” - Dinkel, John J.; Kochenberger, Gary A. (Management Science, 1974)
The purpose of this paper is to present a computationally attractive view of sensitivity analysis in geometric programming. The approach is motivated by the need to obtain numerical solutions to large-scale geometric programs and provides a summary of some sensitivity analysis results in a readily usable computational form.